A Psychoanalysis Exploration of Character’s Internal Conflict and Childhood Trauma in Jessi Burton’s Medusa - Illahi, Shinta Dzikra; Pratiwi, Dyani Prades (LingoLitera, 2025)
Many people who have experienced childhood trauma generally experience conditions such as depression, anxiety, and post-traumatic stress disorder that can cause internal conflict. This study aims to show the internal conflict in Medusa by Jessi Burton. This study uses a qualitative descriptive method and a psychoanalytic approach. The results of this study show that the traumatic incidents that happened to young Medusa made her feel helpless and ashamed, and she lost her self-confidence, which influenced her way of thinking that everyone who came would immediately leave her and even felt like she would be betrayed again. The traumatic incidents that Medusa experienced continue to haunt her through dreams. Her actions were caused by the internal conflict wherein her Ego attempts to mediate the demands of the impulsive Id and the moralistic Superego. The cause of internal conflict emerged because the dream kept repeating the incident where she was raped and punished by Athena, the Goddess that she served, which made her feel ashamed. Those incidents were why she hid when talking to Perseus and made a fake identity because she was embarrassed by her terrible appearance. The internal conflict in Medusa also influenced how she decides to react to someone who wants to kill her, Perseus. Her hatred for Perseus can be controlled by finally choosing what the superego wants: to forgive Perseus.